Invariance principle for the random conductance model - Andres, S; Barlow, M; Deuschel, J; Hambly, B (2013)
We study a continuous time random walk X in an environment of i.i.d. random conductances Mathematical expression in Mathematical expression . We assume that Mathematical expression, so that the bonds with strictly positive conductances percolate, but make no other assumptions on the law of the μ . We prove a quenched invariance principle for X, and obtain Green's functions bounds and an elliptic Harnack inequality. © 2012 Springer-Verlag.